Estudio epidemiológico de varroasis en abejas adultas (Apis mellifera) en el cantón Loja. - Arévalo Soto, Jorge Livio (2018)
This research study was carried out in apiaries of the Loja Canton, province of Loja. The objectives were to determine the prevalence of Varroa destructor (Varroa mite) in adult bees (Apis mellifera) and the risk factors associated with parasitism. A prevalence of 100% was determined in apiaries and hives, with a confidence interval of 95%, where 15.28% of the hives were found with an infestation level higher than 5%, and 205 hives (84.71 %) were found with a level of infestation of less than 5%. 54 epidemiological surveys were carried out (one for each apiary) with a bank of questions considered as possible risk factors for the presentation of the disease. Through logistic regression, it was determined that being within the Vilcabamba district increased the risk of varroosis infestations by 5% in relation to the other districts of the canton (OR = 13.05). Also, the risk increased when the apiaries owners were not advised by a technician (2.04). The risk of varroosis infestations over 5% decreased when visits were made by the beekeeper every 30 days rather than on biweekly visits (OR = 0.39) and when underbrush clearing was performed at intervals greater than 20 days (OR = 0,41). The variables:  area of the holding, use of beeswax, close apiaries, number of harvests per year, number of reserve frames, use of food supplements, removal of honey supers, diseases that occurred during the previous year, use of records, capture of swarms, mortality during the previous year and type of treatment used for varroosis were not considered statistically significant (p> 0.05). Keywords: Varroa destructor, Prevalence, Risk factors.